2019
DOI: 10.1101/529289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial volume fraction controls translation of nuclear-encoded mitochondrial proteins

Abstract: Mitochondria are dynamic in their size and morphology yet must also precisely control their protein composition according to cellular energy demand. Although nuclear-encoded mRNAs can be localized to the mitochondrial outer membrane, the importance of this localization in altering mitochondrial protein composition is unclear. We have found that, as yeast switch from fermentative to respiratory metabolism, there is an increase in the fraction of the cytoplasm that is mitochondrial. This drives the localization … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…While still relying on ribosome association, these mechanisms do not depend on some property in the nascent protein. Such ribosome association-dependent localization of transcripts has also been described for organelles other than the ER, such as mitochondria 5,6,7 . To identify mRNA-associated factors that might be involved in the case of EEA1 transcript targeting to endosomes, we developed an assay for the specific isolation of endogenous EEA1 transcripts together with its associated proteome.…”
Section: Silac-based Proteomics Of Eea1 Mrna Reveals Rna-binding Protmentioning
confidence: 58%
“…While still relying on ribosome association, these mechanisms do not depend on some property in the nascent protein. Such ribosome association-dependent localization of transcripts has also been described for organelles other than the ER, such as mitochondria 5,6,7 . To identify mRNA-associated factors that might be involved in the case of EEA1 transcript targeting to endosomes, we developed an assay for the specific isolation of endogenous EEA1 transcripts together with its associated proteome.…”
Section: Silac-based Proteomics Of Eea1 Mrna Reveals Rna-binding Protmentioning
confidence: 58%
“…Mechanisms to control initiation efficiency of a mitochondrial-localized regulon could include intracellular magnesium concentration (73), variations in availability or modification status of shared initiation factors, variations of the ratio of mitochondrial volume to intracellular volume (74), or specialized factors to promote initiation specifically of mitochondrial isoforms with their specialized start codon context. Nakagawa et al (75) previously suggested that distinct Kozak contexts might be recognized by different molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, localization of many mRNAs to mitochondria was shown to depend on their translation and the presence of the Tom20 receptor that binds MTSs [22,44]. If a transcript is very long or translation is slowed down by rare codons, RNCs that already synthetized an MTS may have time to associate with mitochondria [45]. However, it was proposed that some additional factors may specifically recruit RNCs to the mitochondrial OMs and act via binding the ribosome itself [46,47].…”
Section: Cotranslational Targetingmentioning
confidence: 99%